ANALISIS EKUITAS MEREK MINUMAN TEH HIJAU DALAM KEMASAN SIAP MINUM NU GREEN TEA TERHADAP FRESTEA GREEN DAN JOYTEA GREEN DI KOTA BENGKULU - Sartika, Burenida; Asrani, Putri Suci; Andani, Apri (Jurnal AGRISEP, 2013)
The research was conducted during April to June 2012. Primary and secondary data were used in this research. The primary data related to respondent demography and brand equity.   One hundred respondents were selected accidentally around Bengkulu city.  Data were analysed quantitatively and qualitatively.  Quantitative data were processed using Test of Validity, Reliability Test (Hoyt), Cochran Test Analysis, Importance Performance Analysis (IPA), and Brand Switching Matrix Pattern.  The result of the research showed that the NU Green Tea brand is the highest one, and 48% Top of Mind value. Brand Recall in Frestea Green get 45,8%.  Brand Recognition asserts 75% among respondences to the existence of  Joytea brand. The result of Unaware Brand reveals the research doesn’t seem to know Joytea Brand. Analyzing of Branded Association declares that NU Green Tea has 12 brand associations, Frestea Green brand has 10 brand associations, and in other side Joytea Green brand has 7 brand associations which each made brand image. More results for associations Cochran testing, means the consumers aware to the attributes of the product. It’s included that NU Green Tea brand of drinking package has most of the brand image than  Frestea and Joytea Green. Consumer’s perceptions analyzing reveals that NU Green Tea has a good effort as to the respondents want to. Frestea Green must to get more effort to satisfy consumers. At least Joytea Green brand should be awared enough to increase their ability to get more result in consumer satisfying.  Consumers’ loyalty analysis showed that the Frestea brand has good consumers loyalty than NU Green Tea and Joytea Green brand.